THE ROLE OF ISLAMIC BANKING IN FINANCING LOCAL DEVELOPMENT: A STUDY IN THE ALGERIAN EXPERIENCE - Nacir Yahia Cherif; Aouragh Reguia; Kabahoum Sami (International Journal of Innovative Technologies in Social Science, 2024)
The aim of this article is to review the extent to which Islamic banking can contribute to the financing of local development in Algeria, by financing economic investments, where it is based on the formation of an investment pot in significant amounts, where these funds are transferred from hoarding space to production and development.Algeria has made every effort to advance the process of development by adopting Islamic banking as a viable financing alternative by adopting the Bank of Algeria's 20-02 banking system for Islamic banking and its rules of practice. This article concludes that Islamic banking can play an important role in comprehensive domestic development by providing various financing formats suitable for all types of investment.